Study of Factors Causing Compliance in Taking Medication for Diabetes Patients - Widyawati, Bobby; Wardha, Fenty; Rosa, Emmilya (CV. Global Health Science Group, 2024)
With 236 million Muslims, or 84.3% of the population, Indonesia is the second largest Muslim country in the world, according to the World Population Review. It is undoubtedly a problem when all risk variables coincide with an activity. Diabetes is a long-term condition that arises from insufficient insulin production by the pancreas or ineffective use of insulin by the body. The purpose of this study was to determine the factors that cause compliance with taking medication for diabetics in the Palembang embarkation Hajj pilgrims. Method is descriptive and uses snowball sampling techniques through recording, interviews, and observations. Results of the total number of prospective hajj pilgrims in 2024, 8,473 have diabetes, 483 of whom are prospective hajj pilgrims through the Palembang Embarkation. The majority of diabetes sufferers are women (54.86% of respondents), while the majority of prospective male hajj pilgrims (45.14%) are men. The most common comorbidities in prospective hajj pilgrims at the Palembang Embarkation are diabetes sufferers under the age of 60 (64.80%), hypertension at 60.19%, and dyslipidemia at 39.81%. It is important to carry out regular health checks to prevent/avoid the emergence of unwanted diseases and to improve the quality of life for the better.